Comparison of energy expenditure of tasks in standing and sitting in adolescent girls. - Dockrell, Sara; Forde, Cuisle; Gormley, John (Work, 2020)
BACKGROUND: Adolescent girls are prone to increased sedentary behavior and are more sedentary than their male peers or younger girls. This study compared the energy required for identical tasks in standing and sitting. METHOD: Energy expenditure (EE) was measured using indirect calorimetry (n = 24) in four tasks (sitting/standing quietly; reading; typing; sorting paper) under two postural conditions (sitting; standing). The currently accepted definition for sedentary behavior of energy expenditure of ≤1.5 metabolic equivalents (METs) and being in a seated or reclining position was used. RESULTS: All seated tasks resulted in mean EE <1.5 METs with the exception of sorting paper. All standing tasks resulted in mean EE of >1.5 METs with the exception of standing quietly. Standing sorting paper was the only task with a mean EE significantly >1.5 METs. A significant interaction between task and posture was found. CONCLUSIONS: Active tasks in standing had significantly greater EE than in sitting, and sorting paper while standing was the only task with an EE significantly >1.5 METs. The difference between the two postures is likely too low to produce positive metabolic health benefits in the short term. Studies of the effects of long-term use of standing desks in the classroom are required.